Model Struktural Kepuasan Mahasiswa Dengan Kualitas Pelayanan Sebagai Variabel Eksogen - Riwoe, Febry Lodwyk Rihe; Mulyana, Mumuh (Jurnal Ilmiah Manajemen Kesatuan, 2020)
High school graduates have many university choices when making further study decisions. Various facilities and advantages offered by universities. The experiences and impressions first obtained when interacting, communicating and transacting with a Unit PMB, can be deeply embedded in the minds of students and the community which has implications for the level of satisfaction. This study aims to measure the effect of physical evidence, empathy, assurance, reliability and responsiveness to the new students’ satisfaction. This quantitative descriptive study used cross sectional primary data from 100 new IBI Kesatuan Students conducted at the beginning of April 2020. The data were analyzed using a partial least square structural equation modeling approach. The results showed that the factors of physical evidence, empathy, reliability and responsiveness significantly affected student satisfaction.